2019
DOI: 10.32598/irj.17.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Challenges in Orthotics and Prosthetics Clinical Learning Environments: A Qualitative Study

Abstract: The present study explored challenges in orthotics and prosthetics clinical learning environments in Iran. Methods: A qualitative content analysis method was used to obtain data on orthotics and prosthetics clinical educator's experiences. Qualitative data were obtained using semistructured in-depth interviews involving 7 clinical educators; all selected by the maximum variation purposeful sampling method. Interviews continued until data saturation. Results: During the interview sessions, notes and ideas were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
(24 reference statements)
0
7
1
Order By: Relevance
“…32 Over the past few decades, Iran has tried to train a suitable number of graduates to meet the needs of the P&O services by developing academic education and establishing scientific departments at medical universities. 17 Our study findings, however, showed that these graduates were reluctant to work in disadvantaged and remote areas and preferred to work in larger cities. Unfavorable working conditions in small and remote cities were considered as one of the reasons for unwillingness to work in such areas.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…32 Over the past few decades, Iran has tried to train a suitable number of graduates to meet the needs of the P&O services by developing academic education and establishing scientific departments at medical universities. 17 Our study findings, however, showed that these graduates were reluctant to work in disadvantaged and remote areas and preferred to work in larger cities. Unfavorable working conditions in small and remote cities were considered as one of the reasons for unwillingness to work in such areas.…”
Section: Discussioncontrasting
confidence: 56%
“…7 However, a limited number of P&O graduates in countries such as Iran have made it difficult to provide these services to the needy, especially in deprived and remote areas. 17,31 This is also seen in Malaysia, where no sufficient trained workforce is available despite a need for at least 640 prosthetists. 32 Over the past few decades, Iran has tried to train a suitable number of graduates to meet the needs of the P&O services by developing academic education and establishing scientific departments at medical universities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education in the field of prosthetics and orthotics (P&O), as one of the rehabilitation disciplines, encompasses two sectors of theoretical and practical-clinical courses [ 11 ]. Furthermore, as in other medical sciences, the internship is unquestionably an essential component of P&O training [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The practice placement provides the opportunity to establish professional and clinical skills, and apply theory into practice (Pitanken et al 2018), and is a key element of Prosthetic and Orthotic (P&O) education programmes. However practice placements are often reported as being the most stressful and challenging element of an undergraduate programme (Shahabi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%